2021
DOI: 10.1037/men0000328
|View full text |Cite
|
Sign up to set email alerts
|

Taking the black pill: An empirical analysis of the “Incel”.

Abstract: Men who perform hybrid masculinities claim distance from masculine hegemony while actually reproducing patriarchal power. In this article, we analyze the Incel community through a lens of hybrid masculinities, as originally proposed by Ging. The Incels are a self-proclaimed group of beta males who claim a position at the bottom of the social hierarchy due to their continued romantic and sexual rejection by women. We performed a content analysis of a sample of 400 top-rated posts from the Incel forum on Reddit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 19 publications
2
60
0
1
Order By: Relevance
“…Regardless, the evidence here lends support to claims that unemployed men who have yet to establish residential independence from their parents have less currency in the heterosexual dating market. While population surveys like the NSFG are not well-equipped to identify and study fringe subcultures, the general narrative regarding socially disengaged men emerging from the nascent body of media coverage (Dickson, 2020) and research (Glace et al, 2021;Preston et al, 2021) on incels is generally supported here.…”
Section: Discussionmentioning
confidence: 87%
“…Regardless, the evidence here lends support to claims that unemployed men who have yet to establish residential independence from their parents have less currency in the heterosexual dating market. While population surveys like the NSFG are not well-equipped to identify and study fringe subcultures, the general narrative regarding socially disengaged men emerging from the nascent body of media coverage (Dickson, 2020) and research (Glace et al, 2021;Preston et al, 2021) on incels is generally supported here.…”
Section: Discussionmentioning
confidence: 87%
“…The authors report an increase in incel-related activity on YouTube, and that incelrelated videos attract a substantially larger number of negative comments compared to other videos. Glace et al (2021) performed a content analysis of 400 top-rated posts from /r/ Braincels and found that hostile sexism was an inductive theme in the conversations, including shaming women's appearances, degrading women for engaging in sexual activity, suggesting that women make false claims of rape and misogyny, asserting that women's only value is sexuality, and dehumanization of women. Another inductive theme identified by the authors was suicidality/meaninglessness.…”
Section: State Of the Artmentioning
confidence: 99%
“…One of the most well-known is offender is Elliot Rodger, a young man who killed six people in Southern California after posting a video online in which he stated that his violent actions were motivated by his experiences of social rejection, especially romantic rejection from women. Rodger later died by suicide and became seen as a martyr by many in the incel community (Glace et al 2021). Another attack was done by self-identified incel in Toronto, Canada, who drove a van into a crowd of people, killing 10 (Beauchamp 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A quarter (25%) of threads analyzed in one study contained ''it's over'', reflecting users' lack of hope of escaping their predicament, a view also expressed by discussion of the blackpill (Jaki et al, 2019). Congruent with this fatalistic outlook, several members of these forums have openly discussed their suicidal thoughts and plans online (Baele, Brace, & Coan, 2019;Cottee, 2020;Daly & Laskovtsov, 2021;G. Glace, T. L. Dover, & J. G. Zatkin, 2021;Hoffman et al, 2020;Jaki et al, 2019;Jones, 2020;Maxwell et al, 2020;Rubertsson, 2019;Speckhard et al, 2021;Williams, 2020).…”
Section: Qualitative Studies Providing Psychosocial Data On Incelsmentioning
confidence: 99%